2017
DOI: 10.21608/jppp.2017.46157
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Soft Scale Insect Kilifia acuminata (Signoret) (Hemiptera: Coccidae) is a Main Insect Pest Attacking Mango Trees.

Abstract: The soft scale insect kilifia acuminata (Signoret) (Hemiptera: Coccidae) is one of the main insect pests infesting mango trees and caused the damage for leaves and fruits. The population density of the soft scale insect k. acuminata during the first year of study 2014/15 recorded 6 peaks and the highest peak was 1539 indiv.on 27 th of March, 2015. While recorded 5 peaks during the second year 2015/16 and the highest peak was on 17 th of June 2016 and represented by 1178 indiv. The highest average number and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
0
0
Order By: Relevance
“…Attia and Ramadan (2013) indicated that the highest peak of this insect was recorded in April. Awadalla et al, (2017) mentioned that the highest peak of the soft scale K. acuminate occurred in March at Kafr-El-Sheikh Governorate, and the lowest one was recorded in June. Throughout the present period of study, only on parasitoid species (the endoprasitoid, Metaphycus zebratus (Mercet).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attia and Ramadan (2013) indicated that the highest peak of this insect was recorded in April. Awadalla et al, (2017) mentioned that the highest peak of the soft scale K. acuminate occurred in March at Kafr-El-Sheikh Governorate, and the lowest one was recorded in June. Throughout the present period of study, only on parasitoid species (the endoprasitoid, Metaphycus zebratus (Mercet).…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes concurred with those of Elwan (1990), who recorded that the lower and middle parts of the tree were preferable to this insect over the upper part. Awadalla et al, (2017) found that the lowest numbers were recorded in the north direction of the tree in Kafr-El-Sheikh Governorate.…”
Section: Distribution Of the Insect Population According To The Main ...mentioning
confidence: 93%
See 1 more Smart Citation